2021
DOI: 10.1097/md.0000000000028245
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis caused by tigecycline

Abstract: Rationale: There is evidence that tigecycline has broad-spectrum antibiotic activity against a variety of complicated infections. However, adverse effects are inevitable, including gastrointestinal side effects such as nausea, vomiting, and diarrhea; in 2006, acute pancreatitis was also brought into the side-effect list after postmarketing surveillance. Here, we present a case of tigecycline-induced acute pancreatitis. Patient concerns: An 87-year-old female patient wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Four patients (11.8%) died, of whom two died from severe pancreatitis complications, 26 , 31 and two died of cardiogenic shock and septicemia. 22 , 30…”
Section: Resultsmentioning
confidence: 99%
“…Four patients (11.8%) died, of whom two died from severe pancreatitis complications, 26 , 31 and two died of cardiogenic shock and septicemia. 22 , 30…”
Section: Resultsmentioning
confidence: 99%
“…Tigecycline, a derivative of the tetracycline class of drugs, was first approved by the Food and Drug Administration in 2005 for the treatment of various types of infections, such as skin and soft tissue infections, intra-abdominal infections, and bacterial pneumonia. Developed to overcome the common mechanisms of resistance such as ribosomal protection and efflux pumps [ 3 ], tigecycline's safety profile initially listed adverse effects such as nausea, vomiting, and diarrhea. However, it wasn't until a retrospective cohort study and a review of phase III trials that pancreatitis was identified as a potential adverse effect [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the rise of multidrug-resistant organisms, tigecycline's ability to inhibit these organisms in vitro has led to its off-label use for the treatment of these infections [ 4 ] and may be contributing to the rise in the incidence of pancreatitis. Several mechanisms have been proposed to explain the link between tigecycline use and pancreatitis, including the production of toxic metabolites, elevation of triglyceride levels, and high drug accumulation in the biliary system [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations